Development of learning media based on local wisdom to improve the ability to write poetry for grade VIII students - Haslinda (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The development of learning media that integrates local wisdom has an important role in enriching the learning process, especially in poetry writing skills that reflect local cultural values. This research aims to (1) develop learning media based on local wisdom, and (2) test the validity and effectiveness of learning media based on local wisdom in improving the poetry writing skills of grade VIII junior high school students. This study used a research and development (R&D) approach with a 4-D model consisting of (1) Define, (2) Design, (3) Develop, and (4) Disseminate. The subject of this study is students of grades VIII Junior High School of the University of Muhammadiyah Makassar which consists of 5 classes. The data collection method in the study used questionnaires used to analyze student needs, product validity tests by experts, and product effectiveness tests. The analysis technique used in this study was quantitative descriptive. The results of the study show that learning media based on local wisdom has a valid category, which is evidenced by a percentage of 90% with a very valid category from media experts. The results of the validity test from material experts showed a percentage of 92% with a very feasible category. The results of the validity test from linguists showed a percentage of 92.5% with a very valid category. The results of the effectiveness test were carried out by involving individual subjects, small groups, and large groups. The results showed that the percentage of effectiveness was 88% with a valid category for individual trials, the results of small group trials were 92% with a very valid category, and the results of large group trials were 94% with a very valid category. The development of learning media based on local wisdom has proven to be effective in improving the poetry writing ability of Class VIII students as well as fostering appreciation for regional culture.